Alface americana submetida à adubação nitrogenada e tensões de água no solo em ambiente protegido - Carvalho, Kassio dos Santos (2013)
Lettuce is a culture demanding in water consumption and the irrigation appropriate management is major, as well as nitrogen fertilization because nitrogen is a nutrient that stimulates plant development. This study aimed to evaluate the effect, isolated and associated soil water tensions and nitrogen levels applied in a Grossense Mato Cerrado of red oxisol with the development of the culture of lettuce under controlled conditions. The experiment was conducted in pots with capacity for 7 dm3 of soil end in greenhouse. The experimental design was completely randomized in a 4x5 factorial design, with 20 treatments (15, 30, 45, and 60 kPa soil water tension and 0, 50, 100, 150 and 200 mg dm-3 nitrogen) and four replications. The nitrogen source used to urea and tensions were controlled by tensiometers installed at 10 cm depth in the experimental units fertilized with 100 mg dm-3 nitrogen. The analyzed variables were: leaves and total aerial parts of green weight, of leaves number, weight dry leaf, total and root, chlorophyll content, of plant height and leaf area. The results were subjected to analysis of variance and when significant regression, both 5% probability. In general, the further development of variable of leaves green weight and total dry mass of leaves, root and total of number leaves and leaf area was observed in the soil water tension of 15 kPa. The biggest plant height and chlorophyll content was checked with application 66.75 and 107.67 mg dm-3 of nitrogen, respectively. The root dry weight decreased with increasing nitrogen fertilization. The chlorophyll content and root dry weight showed interaction between the water tension in the soil and the nitrogen.